Integration of Neuroscience Principles in Science Learning Media: A PICO-Based Systematic Literature Review - Winarni, Susi; Supena, Asep (PT. Banjarese Pacific Indonesia, 2026)
Science education at the elementary school level plays a crucial role in fostering scientific thinking, curiosity, and problem-solving skills from an early age. Nevertheless, science instruction in elementary schools often remains teacher-centered, verbalistic, and insufficient in promoting meaningful scientific literacy. In response to these challenges, neuroscience provides a theoretical and empirical foundation for designing learning media that align with how the brain processes, stores, and retrieves information. This study aims to systematically examine the integration of neuroscience principles into science learning media and their effects on elementary students' scientific literacy. A Systematic Literature Review (SLR) was conducted using the PICO framework (Population, Intervention, Comparison, Outcome). Relevant peer-reviewed studies published between 2019 and 2024 were retrieved from Scopus, Google Scholar, ERIC, and DOAJ databases. The review followed four stages: identification, selection, quality appraisal, and thematic synthesis. The results indicate that neuroscience-based interventions—such as Augmented Reality (AR), Brain-Based Learning (BBL), interactive multimedia, and multisensory instructional strategies—consistently improve students' motivation, attention, conceptual understanding, critical thinking, and scientific literacy compared to conventional instructional approaches. The novelty of this study lies in its systematic synthesis of neuroscience-based science learning media through a PICO-oriented framework, highlighting the interaction between cognitive, affective, and technological dimensions of learning. The findings provide important implications for science education, particularly in guiding the development of neuroscience-informed learning media and instructional designs to enhance scientific literacy in elementary schools.